2022
DOI: 10.1109/jeds.2022.3185324
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Switching Dynamics in STT-MRAM

Abstract: In this paper a new experimental technique for measuring the switching dynamics and extracting the energy consumption of Spin Transfer Torque MRAM (STT-MRAM) device is presented. This technique is performed by a real-time current reading while a pulsed bias is applied. The switching from a high resistive state, anti-parallel (AP) alignment, to a low resistive state, parallel (P) alignment, is investigated as well as the impact of the cell diameter on the switching parameters. We demonstrate that preswitching a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…This is coherent with the fact that the AP state is known to be less stable than P state [16,17]. We also notice that the activation energy slightly decreases with the applied voltage since less energy is required to reach the switch for high applied voltages [13]. For the P to AP transition at low applied voltage (VA=-0.45V), the activation energy is higher (above 4eV) showing a different mechanism, probably due to self-heating of the device as evidenced in [18].…”
Section: Temperature Characterizationsupporting
confidence: 81%
See 4 more Smart Citations
“…This is coherent with the fact that the AP state is known to be less stable than P state [16,17]. We also notice that the activation energy slightly decreases with the applied voltage since less energy is required to reach the switch for high applied voltages [13]. For the P to AP transition at low applied voltage (VA=-0.45V), the activation energy is higher (above 4eV) showing a different mechanism, probably due to self-heating of the device as evidenced in [18].…”
Section: Temperature Characterizationsupporting
confidence: 81%
“…This parameter depends on the applied voltage and temperature. A previous study [13] on the preswitching time for the AP to P transition at room temperature, showed a large variability on t , which seems random for a given V * . This paper will focus on demonstrating the stochasticity of both transitions.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations